Paramedic Global Impression of Change During Prehospital Evaluation and Transport for Acute Stroke. Issue 3 (March 2020) - Shkirkova, Kristina; Schuberg, Samuel; Balouzian, Emma; Starkman, Sidney; Eckstein, Marc; Stratton, Samuel; Pratt, Franklin D.; Hamilton, Scott; Sharma, Latisha; Liebeskind, David S.; Conwit, Robin; Saver, Jeffrey L.; et al.
Abstract : Background and Purpose—: The prehospital setting is a promising site for therapeutic intervention in stroke, but current stroke screening tools do not account for the evolution of neurological symptoms in this early period. We developed and validated the Paramedic Global Impression of Change (PGIC) Scale in a large, prospective, randomized trial. Methods—: In the prehospital FAST-MAG (Field Administration of Stroke Therapy-Magnesium) randomized trial conducted from 2005 to 2013, EMS providers were asked to complete the PGIC Scale (5-point Likert scale values: 1-much improved, 2-mildly improved, 3-unchanged, 4-mildly worsened, 5-much worsened) for neurological symptom change during transport for consecutive patients transported by ambulance within 2 hours of onset. We analyzed PGIC concurrent validity (compared with change in Glasgow Coma Scale, Los Angeles Motor Scale), convergent validity (compared with National Institutes of Health Stroke Scale severity measure performed in the emergency department), and predictive validity (of neurological deterioration after hospital arrival and of final 90-day functional outcome). We used PGIC to characterize differential prehospital course among stroke subtypes. Results—: Paramedics completed the PGIC in 1691 of 1700 subjects (99.5%), among whom 635 (37.5%) had neurological deficit evolution (32% improvement, 5.5% worsening) during a median prehospital care period of 33 (IQR, 27–39) minutes. Improvement was associated with diagnosis of cerebral ischemia rather than intracranial hemorrhage, milder stroke deficits on emergency department arrival, and more frequent nondisabled and independent 3-month outcomes. Conversely, worsening on the PGIC was associated with intracranial hemorrhage, more severe neurological deficits on emergency department arrival, more frequent treatment with thrombolytic therapy, and poor disability outcome at 3 months. Conclusions—: The PGIC scale is a simple, validated measure of prehospital patient course that has the potential to provide information useful to emergency department decision-making. Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00059332.